(untitled) (Jurnal Teknologi (Sciences & Engineering), 2013)
Amorphous carbon (a-C:H/a-C) or Diamond-like carbon (DLC), has a very high potential diverse engineering and medical application for high wear resistance and tribological performance. Naturally grown columnar DLC films is chemically modified by post-treatment via electron beam irradiation (EB-irradiation), through precise observation and characterization by field emission scanning electron microscopy (FE-SEM), atomic force microscopy (AFM), and Raman spectroscopy. This nano-columnar a-C:H film has a unique nano-structure and mechanical properties. This nano-columnar structure is composed of graphitic inter-columnar network with amorphous carbon columns. Metallic doping into the inter-columns reflects positively on mechanical response by chemical modification with physical hardening.